2014
DOI: 10.1038/nrendo.2014.73
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids and fetal programming part 1: outcomes

Abstract: Fetal development is a critical period for shaping the lifelong health of an individual. However, the fetus is susceptible to internal and external stimuli that can lead to adverse long-term health consequences. Glucocorticoids are an important developmental switch, driving changes in gene regulation that are necessary for normal growth and maturation. The fetal hypothalamic-pituitary-adrenal (HPA) axis is particularly susceptible to long-term programming by glucocorticoids; these effects can persist throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
419
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(437 citation statements)
references
References 154 publications
14
419
2
2
Order By: Relevance
“…Elevations in perceived stress and cortisol concentrations have been related to higher concentrations of pro-inflammatory cytokines and lower concentrations of anti-inflammatory cytokines [44,45]. In the longer-term, excess glucocorticoid exposure has been associated with the life-long function of the HPA axis in the offspring, and has been hypothesized to increase susceptibility to a variety of conditions including depression, hypertension, type 2 diabetes mellitus, and cognitive impairments [42,46]. The fetus is somewhat buffered from the effects of high maternal cortisol concentrations through the activity of the 11-β-hydroxysteroid dehydrogenase (HSD)-2 enzyme in the placenta, which converts maternal cortisol to an inactive cortisone [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevations in perceived stress and cortisol concentrations have been related to higher concentrations of pro-inflammatory cytokines and lower concentrations of anti-inflammatory cytokines [44,45]. In the longer-term, excess glucocorticoid exposure has been associated with the life-long function of the HPA axis in the offspring, and has been hypothesized to increase susceptibility to a variety of conditions including depression, hypertension, type 2 diabetes mellitus, and cognitive impairments [42,46]. The fetus is somewhat buffered from the effects of high maternal cortisol concentrations through the activity of the 11-β-hydroxysteroid dehydrogenase (HSD)-2 enzyme in the placenta, which converts maternal cortisol to an inactive cortisone [47].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the drugs used in the treatment of HIV can also interfere with adrenal function [31]. Cortisol response to stressors is generally blunted during pregnancy [40] Despite the physiologic explanations for a normal rise in cortisol during pregnancy, higher than expected increases in cortisol and CRH concentrations have important short-and long-term negative functional consequences on the health of the pregnancy and the offspring in later life [41,42]. In the short term, elevated CRH is associated with placental dysfunction, including shallow trophoblast invasion and poor placental vascularization which can lead to intrauterine growth restriction and preeclampsia [43].…”
Section: Discussionmentioning
confidence: 99%
“…The result is a decrease in the charge cAMP, decreased activation of PKA will phosphorylate a variety of proteins. The result is a decrease in the stimulation of rate-limiting step (limiting step rate) on the formation of cortisol through the conversion of cholesterol to pregnenolone which is catalyzed by the enzyme side-chain cleavage/SCC (breaker side chains) cholesterol (White 2010, Moisiadis & Matthews 2014, Barrett 2012.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease Ca2+ resulted in a decrease in ACTH exocytosis. Suppression of ACTH release is also caused by resistance POMC synthesis (White 2010, Moisiadis & Matthews 2014, Barrett 2012.…”
Section: Discussionmentioning
confidence: 99%
“…This hormone elevation could give rise to an early shift from cell proliferation to cell differentiation in the immune system, with an inappropriate pattern of growth for the stage of development and possible adverse consequences much later in life. 32,33 Altered HPA activity was reported to be a possible underlying mechanism in an animal model study that found a transgenerational effect of maternal treatment with dexamethasone, a common clinical practice in pregnancies at risk of preterm birth: first filial generation and second filial generation ewe lamb offspring showed an increased baseline but reduced stimulated HPA activity. 34 Another pathway through which maternal nutrition has broad relevance for immune-mediated diseases is represented by the link between a lack of omega-3 fatty acids during pregnancy and the suppression of interleukin 13 a Cases with gestational age <37 and >41 weeks were grouped together on the basis of the results of the univariate analysis (Table 2), which showed no statistical difference between each of these groups and the reference category.…”
Section: Commentmentioning
confidence: 99%